Unraveling the Interplay of Language and Culture in BIPA Learning for International Students - Febria, Feby; Tiawati, Refa Lina; Rahmat, Wahyudi (Journal of Humanity Studies, 2023)
This research aims to describe the role of language and culture in the success of international students in BIPA learning at AndalasUniversity. The method used in this research is descriptive. The data used is data obtained from observations, interviews and documentation on the role of language and culture with BIPA students at Andalas University. Data collection techniques use observation, interviews and documentation techniques. The data source in this research is interviews with Andalas University students. According to the results of the analysis, it was found that 24 language roles and 30 cultural roles were known to Andalas University international students.